Mechanical properties of cement brick using quarry dust as partial sand replacement - Muhammad Azfar, Bahaudin (2017)
An environmentally sustainable system must maintain a stable resource base avoiding over-exploitation of non-renewable resource system. This experimental study presents the variation in the compressive strength, flexural strength and water absorption of bricks when quarry dust is used to replace sand in cement brick production. Four types of mix proportions were practiced in the production of the bricks specimens were 1:5:0, 1:4.9:0.1, 1:4.8:0.2 and 1:4.7:0.3 (Cement: Sand: Quarry Dust). Method that used for the curing of the bricks is ponding method. The compressive and flexural strength of the bricks was determined at 7, 14 and 28 days. Both compressive and flexural strength give the highest strength at 30%. The compressive and flexural strength increased gradually with the increase of quarry dust that used as partial san replacement. The water absorption test decrease gradually as the percentage of quarry dust decrease. This give the 30% of quarry dust used as partial sand replacement has the lowest water absorption. Hence 30% of quarry dust are the best cement brick from this experimental as it gives higher compressive and flexural strength with the lowest water absorption t percentage.